Indonesia's Position in Navigating the Stability of the Indo- Pacific Region Through Multilateral Cooperation between RCEP and IPEF - Fera Sandrina; Anggi Prastyono (Kementerian Luar Negeri Republik Indonesia, 2024)
This paper explores the Indo-Pacific region's complex landscape, characterized, among others, by the presence of two significant economic forums: the Regional Comprehensive Economic Partnership (RCEP) and the Indo-Pacific Economic Framework (IPEF). This coexistence has the potential to create tensions among member nations, prompting an examination of Indonesia's strategic positioning within these forums. Using the balance of power and foreign policy framework, this qualitative research paper examines the geopolitical implications of these multilateral agreements on Indonesia's position. This paper found that despite Indonesia's foreign policy leaning towards an Inward-looking approach, it remains committed to upholding the spirit of multilateralism within the Indo-Pacific economic architecture. This commitment reflects an acknowledgment of the region's diversity while ensuring inclusivity. Indonesia's overarching objective is to foster positive interdependence among regional nations by nurturing close economic collaboration, thereby contributing to the long-term peace and prosperity of the Indo- Pacific region.